Extreme marine heatwaves and cold-spells events in the Southern North Sea: classifications, patterns, and trends - Mohamed, Bayoumy; Barth, Alexander; Alvera-Azcárate, Aida (Frontiers in Marine Science, 2023)
In this study, we examined the long-term spatiotemporal trend of marine heatwaves (MHW) and marine cold spells (MCS) characteristics in the southern North Sea over the last four decades (1982-2021). We then estimated the difference between their annual mean values and the possible relationship with the large-scale climate modes of natural sea surface temperature (SST) and atmospheric variability using satellite SST data. The SST warming rate was 0.33 ± 0.06°C/decade and was associated with an increase in MHW frequency (0.85 ± 0.39 events/decade) and a decrease in MCS frequency (-0.92 ± 0.40 events/decade) over the entire period. We found a distinct difference between the annual mean values of MHW and MCS characteristics, with a rapid increase in total MHW days (14.36 ± 8.16 days/decade), whereas MCS showed an opposite trend (-16.54 ± 9.06 days/decade). The highest MHW frequency was observed in the last two decades, especially in 2014 (8 events), 2020 (5 events), and 2007 (4 events), which were also the warmest years during the study period. Only two years (2010 and 2013) in the last two decades had higher MCS frequency, which was attributed to the strong negative phase of the North Atlantic Oscillation (NAO). Our results also show that on the annual scale, both the East Atlantic Pattern (EAP) and the Atlantic Multidecadal Oscillation (AMO) play a more important role in the formation of the MHW in the southern North Sea than the other teleconnections (e.g., the NAO). However, the NAO made the largest contribution only in the winter. Strong significant (p < 0.05) positive/negative correlations were found between oceanic and atmospheric temperatures and the frequency of MHW/MCS. This suggests that with global warming, we can expect an increase/decrease in MHW/MCS occurrences in the future.